A review of the botany, ethnopharmacology, phytochemistry, analysis method and quality control, processing methods, pharmacological effects, pharmacokinetics and toxicity of codonopsis radix - Dong, Jiaojiao; Na, Yexin; Hou, Ajiao; Zhang, Shihao; Yu, Huan; Zheng, Senwang; Lan, Wei; Yang, Liu (Frontiers in Pharmacology, 2023)
Codonopsis Radix, a traditional Chinese medicine in China, has great medicinal and scientific value. Moreover, it can also be used as a health product in daily diet. This paper reviews the botany, ethnopharmacology, phytochemistry, analysis method and quality control, processing methods, pharmacological effects, pharmacokinetics and toxicity related to Codonopsis Radix. The information of Codonopsis Radix is obtained from scientific databases (such as Baidu Scholar, CNKI, Google Scholar, PubMed, Science Direct, Web of Science, and SciFinder Scholar), Chinese herbal classics, Chinese Pharmacopoeia, PhD and MSc dissertations, and so on. The chemical components mainly include alkaloids, alkynes and polyacetylenes, flavonoids, lignans, steroids, terpenoids, organic acids, volatile oils, saccharides and other components, which have a wide range of neuroprotective effects, protection of gastrointestinal mucosa and anti-ulcer, regulation of body immunity, anti-tumor, endocrine regulation, improvement of hematopoietic function, cardiovascular protection, anti-aging and antioxidant effects. In conclusion, this paper summarizes in depth the shortcomings of the current research on Codonopsis Radix and proposes corresponding solutions. At the same time, this paper provides theoretical support for further research on the biological function and potential clinical efficacy of Codonopsis Radix.